(untitled) (Sirte University Journal of Humanities, 2026)
This study aimed to investigate the variables influencing available wheat consumption in Libya using time series data from 1970 to 2023 and applying the ARDL model for this purpose. The results indicated that the variables were stationary at level, except for wheat import, which was stationary at the first difference. The study findings also revealed that there is a cointegrating relationship among the variables. Furthermore, the variables influencing consumption had a positive a significant impact in the short-run. In the long run, the aforementioned variables had a significant positive impact, while the population variable had no significant impact. The study recommended increasing wheat production areas in public projects, which would reduce imports, their high costs, and their impact on the trade balance. It also recommended providing support to private sector farmers to encourage production. Finally, it suggested conducting specialized studies to develop suitable high-yield varieties suited to local environmental conditions.